2021
DOI: 10.1590/1809-4430-eng.agric.v41n5p496-503/2021
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Responsiveness of Sugarcane Cultivars Under Irrigated and Rainfed Production Systems

Abstract: Sugarcane is grown in several countries and environmental conditions, and production increases should not only be based on the expansion of the cultivated area. As water is a limiting factor for sugarcane yield, irrigation is crucial to increase its yields. Thus, this study aimed to evaluate the agronomic performance of five sugarcane cultivars under irrigated and rainfed conditions and compare yields in each treatment with those of previous cycles. The experiment was carried out from July 2017 to July 2018, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Chemigation with TFN is able to avoid this problem, since at each application, an amount of the herbicide is accumulated near the emitter's outlet, forming an acidic environment which can inhibits root growth and, consequently, its intrusion into the emitters orifice (Cai et al, 2019;Lima et al, 2014). This technique has been widely recommended as a preventive in field measure, especially in crops extremely sensitive to water stress, such as sugarcane cultivars (Dalri et al, 2021;Lima et al, 2014;Simões et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Chemigation with TFN is able to avoid this problem, since at each application, an amount of the herbicide is accumulated near the emitter's outlet, forming an acidic environment which can inhibits root growth and, consequently, its intrusion into the emitters orifice (Cai et al, 2019;Lima et al, 2014). This technique has been widely recommended as a preventive in field measure, especially in crops extremely sensitive to water stress, such as sugarcane cultivars (Dalri et al, 2021;Lima et al, 2014;Simões et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the productivity of the crop, the plants contained in two meters of line from each experimental unit were harvest and weighed and their productivity in Mg ha -1 was estimated (Dalri et al, 2021).…”
Section: Parameters Assessedmentioning
confidence: 99%
“…However, the combination of moderate reductions in irrigation water with varieties more tolerant to the deficit of water can provide savings in irrigation costs without reducing the sugar produced. Dalri et al (2021) observed that the correct choice of sugarcane cultivar in an irrigated production system may increase productivity by more than 50%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as soil fertilization might be carried out during the drought season, the use of liquid fertilizer seems more adequate to promote great nutrient accumulation by the plant and sugarcane growth ( Ullah et al., 2019 ) due to the soil moistening promoted by the volume of liquid fertilizer applied (800 to 1000 L ha −1 ). This hypothesis is based on experiments that have investigated sugarcane fertilization, which promotes gains in biomass production and in the technological quality of the raw material ( Rhein et al., 2016 ; Gutiérrez-Miceli et al., 2017 ; Dalri et al., 2021 ). To the best of our knowledge, no published study has investigated the use of liquid NPK fertilizer compared to the solid source on sugarcane biomass production and N, P, and K accumulation.…”
Section: Introductionmentioning
confidence: 99%